Biomarkers and clinical tools in critically ill children: are we heading toward tailored drug therapy?. (June 2012) - Buijs, Erik AB; Zwiers, Alexandra JM; Ista, Erwin; Tibboel, Dick; de Wildt, Saskia N
In pediatric critical care, validated biomarkers are essential for guiding drug therapy. The aim of this article is to present examples of current biomarker developments in its full breadth, including biochemical substances, physiological measurements and clinical scoring tools, with a focus on the field of circulatory, renal and neurophysiologic failure. Within each field we consecutively discuss the rationale for the selected biomarkers, studies in critically ill children, biomarker validation stage and biomarker use or potential use in drug studies and clinical drug dosing. This article demonstrates that there is paucity of properly validated biomarkers. Nevertheless, recent developments in, for instance, the field of sepsis, point us toward a future wherein, for critically ill children, drug therapy may be personalized using proteomic profiling instead of a small number of biomarkers, in order to establish a personal and dynamic disease profile.